2014
DOI: 10.3389/fnhum.2014.00775
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between eye movement and vision develops before birth

Abstract: While the visuomotor system is known to develop rapidly after birth, studies have observed spontaneous activity in vertebrates in visually excitable cortical areas already before extrinsic stimuli are present. Resting state networks and fetal eye movements were observed independently in utero, but no functional brain activity coupled with visual stimuli could be detected using fetal fMRI. This study closes this gap and links in utero eye movement with corresponding functional networks. BOLD resting-state fMRI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…This suggests visual imagery in dreaming of the congenitally blind, because alpha activity attenuation is regarded as an indicator of visual imagery in general ( Lopes da Silva, 2003 ). Furthermore, REM-locked activation in visual brain areas in utero suggests a REM-locked primitive form of vision ( Schöpf et al, 2014 ). (2) In monkeys many binocular REMs are not conjugated ( Zhou and King, 1997 ).…”
Section: Neural and Perceptual Correlates Of Rems During Dreaming Slementioning
confidence: 99%
“…This suggests visual imagery in dreaming of the congenitally blind, because alpha activity attenuation is regarded as an indicator of visual imagery in general ( Lopes da Silva, 2003 ). Furthermore, REM-locked activation in visual brain areas in utero suggests a REM-locked primitive form of vision ( Schöpf et al, 2014 ). (2) In monkeys many binocular REMs are not conjugated ( Zhou and King, 1997 ).…”
Section: Neural and Perceptual Correlates Of Rems During Dreaming Slementioning
confidence: 99%
“…One study examined the relation between fetal eye-movements and fetal brain FC and found that fetal eye-movements were associated to simultaneous networks in visual- and frontal areas of the brain [32]. Very recently, the first study associated fetal FC to prematurity [33] – a relatively common negative birth outcome associated with many complications later in life (e.g., [34]).…”
Section: Potential Of Fetal Fc Researchmentioning
confidence: 99%
“…Considerable research has looked at the relationship between functional MR brain imaging and controlled sensory stimulation and a few of these studies have also incorporated MVA. Schopf et al ( 2014 ) used fMRI technology to study fetal eye movements in utero . Their approach included the use of the random forest machine learning algorithm (Breiman, 2001 ) to classify whether individual pixels were part of the fetal eye.…”
Section: Resultsmentioning
confidence: 99%